An integrated process for utilization of pomegranate wastes — Seeds. (February 2015) - Kalamara, Eleni; Goula, Athanasia M.; Adamopoulos, Konstantinos G.
Abstract: In this work, a new method for pomegranate seeds application was developed based on the ultrasound-assisted extraction of seed oil and its subsequent encapsulation by spray drying. Extraction temperature, solvent/solid ratio, amplitude level, and pulse duration/pulse interval ratio were the factors investigated with respect to extraction yield. Ultrasound was sound to increase extraction yield, but mainly to shorten the treatment time by over 12 times. Different materials were used as encapsulating agents. Ratio of core to wall material, inlet air temperature, drying air flow rate, and feed solids concentration were the factors investigated with respect to encapsulation efficiency. The resulting microcapsules were evaluated in terms of moisture content, bulk density, and rehydration ability. The optimum operating conditions were found to be: wall material, maltodextrin/Tween 80; ratio of core to wall material, 0.23; inlet air temperature, 150 °C; drying air flow rate, 22.8 m 3 /h; feed solids concentration, 30% (w/w). Industrial relevance: Pomegranate seeds, a by-product of pomegranate juice and concentrate industries, present a wide range of pharmaceutical and nutraceutical properties. Therefore, the seeds could have more beneficial applications in food industries instead of being used as animal feed or in commercial cosmetic products. In this work, a new method for pomegranate seeds application was developed based on the ultrasound-assisted extraction of seed oil and its subsequent encapsulation by spray drying. Highlights: A new method for pomegranate seed application in food industries was developed. The ultrasound-assisted extraction of oil from pomegranate seeds was studied. The encapsulation of pomegranate seed oil using different wall materials was studied. The effect of different parameters on the efficiency and the microcapsules properties was studied.